Tratamiento de residuos sólidos domésticos y municipales en el distrito de Santa Rosa de Quives (Canta, Lima) - Gallarday Bocanegra, Tomas Exequiel (2008)
The handling and treatment of solid waste or household and agricultural waste in the District of Santa Rosa de Quives is not equal to that given to other public services. The current management has not interest in eliminating technically domestic solid waste (RSM), is considered insignificant, small-scale generated by the neighborhood district. The treatment in their areas of collection, loaded, transport, deposition and removal, is developed into part of the population, according to their degree or cultural knowledge that has on the topic, it is generated in the annexes, towns and farm units. Initially, the RSD are deposited in cylinders and collectors with municipal logo, are located in the parks, one of these containers is collector of batteries and glass, all of the RSD are removed, loaded, transported and disponed of in an irregular manner, so that staff makes it is exposed to dangers of pollution.